CrowdLink: An Error-Tolerant Model for Linking Complex Records - ZHANG, Chen Jason (Institutional Knowledge at Singapore Management University, 2015)
Record linkage (RL) refers to the task of finding records in a data set that refer to the same entity across different data sources (e.g., data files, books, websites, databases), which is a long-standing challenge in database management. Algorithmic approaches have been proposed to improve RL quality, but remain far from perfect. Crowdsourcing offers a more accurate but expensive (and slow) way to bring human insight into the process. In this paper, we propose a new probabilistic model, namely CrowdLink, to tackle the above limitations. In particular, our model gracefully handles the crowd error and the correlation among different pairs, as well as enables us to decompose the records into small pieces (i.e. attributes) so that crowdsourcing workers can easily verify. Further, we develop efficient and effective algorithms to select the most valuable questions, in order to reduce the monetary cost of crowdsourcing. We conducted extensive experiments on both synthetic and real-world datasets. The experimental results verified the effectiveness and the applicability of our model.